Approximation of ω -integrals of continuous functions defined on the real axis by Fourier operators - Sokolenko, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We obtain asymptotic formulas for the deviations of Fourier operators on the classes of continuous functions C^ψ_∞ and C^ψ H_ω in the uniform metric. We also establish asymptotic laws of decrease of functionals characterizing the problem of the simultaneous approximation of ψ-integrals of continuous functions by Fourier operators in the uniform metric.